An experimental study of a very high-pressure diesel injector (up to 5000 bar) by means of optical diagnostics. (1st September 2020) - Vera-Tudela, W.; Haefeli, R.; Barro, C.; Schneider, B.; Boulouchos, K.
Graphical abstract: Highlights: High injection pressures up to 5000 bar were achieved under different conditions. Schlieren, Mie-scattering and OH* chemiluminescence techniques were applied. Injection rates up to 4000 bar of injection pressure present fast opening needle. Highest injection pressures create shock waves inside the chamber improving mixing. Increased mixing and shorter ignition delay times are achieved at higher pressures. Abstract: The aim of this work is to investigate a novel very high-pressure diesel injector under different working conditions. Furthermore, the aim of this work is also to analyse the behaviour of the evaporation, mixing and combustion of a diesel spray in a quiescent environment at very high injection pressures. In order to achieve this, the injector was first characterized from 2500 bar to 4000 bar of injection pressure. Then, an experimental matrix was designed to study the high-pressure spray under (i) cold non-evaporating, (ii) evaporating non-reactive and (iii) reactive conditions under different injection pressures up to 5000 bar. The experiments were carried out in a constant volume cell equipped with optical accesses. This allowed the application of the schlieren, mie-scattering and OH* chemiluminescence techniques at high speed to quantify the propagation of the spray through the ambient gases. The injector used was a prototype single-hole axial injector working with reference diesel as the injection fluid. The results showed a strong dependency of the spray tip penetration on the injection pressure. In some conditions creating shock waves inside the chamber that would disrupt the spray flow, causing it to mix better. Although the higher exit velocities made the fuel travel faster, resulting in longer penetrations of both phases, it also caused the fuel to evaporate faster due to slightly better mixing, resulting in similar liquid length values. This increased momentum enhanced mixing, resulting also in shorter ignition delay times. The higher velocities caused the flame base to stabilise further from the nozzle, which led to longer lift-off lengths.